EFFECTIVENESS OF ACUPUNCTURE IN THE TREATMENT OF URINARY INCONTINENCE: A LITERATURE REVIEW - Tavares de Souza, Maryane; de Azevedo, Monique; Ferreira Mendes, Jones (Health and Society, 2023)
Urinary Incontinence (UI) is the involuntary loss of urine and affects 27% of the world’s population. It is twice as common in women, and in post-menopausal women it reaches up to 70%. The objective of this paper is to expose proof methods of Functional the Pelvic Floor Muscles Training (PFMT) and its interaction, or not, with Acupuncture, in order to verify the effectiveness of Acupuncture in the Treatment of Urinary Incontinence (UI). Among the analysis carried out through virtual surveys and supporting literature, are the definition of UI, description of TMAP and Acupuncture. Traditional treatment methodologies were exposed for each case, as well as physiotherapy and use of needles for the treatment of UI. Throughout the study, the techniques considered by specialists as an adjuvant option to drug treatment were exposed. During the paper conception, this possibility was sometimes combined with the use of Acupuncture. The condition of each group was considered so that a series of results index could be measured. It was noticed that the conduct performed for the treatment of UI along with Acupuncture resources has little to no difference when compared to other therapeutic interventions. Despite being an old problem, UI is neglected and gets concealed due to its convergence with socioeconomic and cultural factors, further corroborating to the non-treatment or application of inappropriate interventions. Acupuncture goes against multimodal therapies and is not effective when conducted in isolation. Therefore, further studies in the area are suggested for a better understanding of the subject.